(untitled) (TAMADDUN NURI JURNALI, 2024)
The article deals with the work of Mahmud Ali Kardari “Nahj ul-farodis” kept in the Suleymaniye library of Turkey, the history of its study, a unique source of Turkish literature of the XIV century.